PENGARUH EDUKASI TERHADAP TINGKAT PENGETAHUAN DAN UPAYA PENCEGAHAN STUNTING ANAK USIA BALITA - Utami, Wuri; Waladani, Barkah; Ernawati, Ernawati (Jurnal Ilmiah Kesehatan Keperawatan, 2024)
The incidence of short toddlers or commonly known as stunting is one of the nutritional problems experienced by toddlers in the world today. Apart from reducing intelligence and productivity and susceptibility to disease, stunting will have the impact of inhibiting economic growth. Therefore, interventions to prevent stunting growth are still needed even after the first 1000 days of birth. This study aims to determine the effect of education on the level of knowledge and efforts to prevent stunting in children under five in the Sempor 2 Community Health Center working area. This research method uses an analytical correlation design with a cross sectional approach. using a pre and post test approach without control. The total sample was 87 respondents with inclusion criteria including mothers of toddlers aged 2-5 years, while the exclusions were mothers who had toddlers with congenital abnormalities, and mothers with toddlers who were acutely ill. This research uses a questionnaire instrument. Before educating respondents, a pre-test was carried out on their level of knowledge and prevention efforts. After being given education, a post test was carried out on the level of knowledge and prevention efforts. The results of the research showed that before the education was carried out, the majority of respondents with a sufficient level of knowledge were 53 respondents (60.9%). After the education was carried out, respondents experienced an increase in their level of knowledge, with 76 respondents (87.3%) in the good category. The results of this study prove that there is an influence of education on increasing knowledge of efforts to prevent stunting in children under five